Conceptualisation of the social agency of youth in sociological studies of the Soviet and post-Soviet periods - Nedelevskaya, Ilona G. (Journal of the Belarusian State University. Sociology, 2024)
The article presents the results of a comparative analysis of the conceptualisation of youth social agency in Western, Soviet and post-Soviet sociology. The problem of social agency is known in sociology within the framework of the structure-action dichotomy. However, for a significant part of history, sociologists tended to focus on the deterministic nature of social structures in individual behaviour. A new assessment of the interdependence of structures and individuals became possible due to historical events and the development of integrative theories in sociology. This problem is becoming increasingly important for scientific communities in many countries due to the increasing dynamics of socio-economic and demographic change. In relation to youth, it is complicated by the incomplete social and epistemic status of this social group in the system of both everyday and scientific perceptions. The article reviews the current state of the problem of youth social agency in Western sociology, explores the conceptualisation of this research topic during the Soviet period, and attempts to establish continuity between modern sociological knowledge on this problem produced by post-Soviet sociologists and the body of Western and Soviet sociological knowledge.
Keywords: social agency; dichotomy of structure and action; social agency of youth; sociology of youth; Soviet sociology; concrete sociological research